IMPLEMENTASI OPTICAL CHARACTER RECOGNITION (OCR) DAN PENDEKATAN THESAURUS UNTUK MENEMUKAN INFORMASI PADA SURAT MASUK DI STMIK STIKOM INDONESIA - I Made Avendias Mahawan; I Putu Agus Eka Darma Udayana (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTSTMIK STIKOM Indonesia currently has 3,953 active students and 1,400 new students entering the academic year 2019/2020. This campus has good cooperation between educational institutions or other non-educational institutions which are indicated through an invitation to attend or participate in activities organized by other institutions. At present, incoming letters or invitations received an average of 50 letters in a month, to simplify the process of incoming letters management, this campus began to make improvements by developing a letter filing system, but the process of handling incoming mails has not been done automatically. Optical Character Recognition (OCR) is one of the technologies that can be used to recognize incoming letter details in the form of letter numbers, letter dates, subject matters, letter destinations and source of letters from the scan results of incoming letters. In this study the researchers proposed OCR technology and a thesaurus approach to be able to obtain information from the results of scans of incoming letters at STMIK STIKOM Indonesia, with 50 test data, the accuracy of recognition obtained from OCR technology will be calculated. The test results using 3 scenarios with the number of thesaurus are 10, 30 and 50, produce the highest level of recognition accuracy that is 92% when using 50 thesaurus.Keywords:OCR, Thesaurus, Incoming Letters, STMIK STIKOM Indonesia.ABSTRAKSTMIK STIKOM Indonesia saat ini memiliki mahasiswa aktif lebih dari 4.000 orang. Kampus ini memiliki kerja sama yang baik antar lembaga kependidikan ataupun lembaga lain non kependidikan yang ditunjukkan melalui undangan menghadiri ataupun mengikuti kegiatan yang diselenggarakan oleh lembaga lain. Saat ini, surat masuk atau undangan yang diterima mencapai rata-rata 50 surat dalam sebulan, untuk mempermudah proses manajemen surat masuk, kampus ini mulai melakukan perbaikan dengan mengembangkan sistem pengarsipan surat, namun proses penanganan surat masuk belum dilakukan secara otomatis. Optical Character Recognition (OCR) merupakan salah satu teknologi yang dapat dimanfaatkan untuk mengenali detail surat masuk berupa nomor surat, tanggal surat, perihal surat, tujuan surat serta sumber surat dari hasil scan surat masuk tersebut. Pada penelitian ini peneliti mengajukan teknologi OCR dan pendekatan thesaurus untuk dapat memperoleh informasi dari hasil scan surat masuk di STMIK STIKOM Indonesia, dengan 50 data uji, maka akan dihitung akurasi pengenalan yang diperoleh dari teknologi OCR. Hasil pengujian menggunakan 3 skenario dengan jumlah thesaurus yaitu 10, 30 dan 50 menghasilkan tingkat akurasi pengenalan tertinggi yaitu 92% saat menggunakan 50 thesaurus.Kata Kunci : OCR, Thesaurus, Surat Masuk, STMIK STIKOM Indonesia